Visible-Light-Induced Difluoromethylation/Cyclization of 1-Acryloyl-2-cyanoindoles by [Bis(difluoroacetoxy)iodo]benzene under Catalyst-Free Conditions - Zhang, Ziqin; Zhao, Yu; Zhang, Zhengting; Zhou, Lin; Lu, Kui; Liu, Zhengyu; Zhao, Xia (Synlett, 2025)
We have developed a visible-light-induced radical cascade difluoromethylation/cyclization reaction of 1-acryloyl-2-cyanoindoles with [bis(difluoroacetoxy)iodo]benzene under catalyst-free conditions. The use of shelf-stable and easily accessible difluoromethylation reagents, combined with environmentally friendly and mild reaction conditions, makes this method an alternative strategy for the synthesis of difluoroalkylated pyrrolo[1,2-a]indolediones.
Keywords: visible-light-induced; difluoromethylation; 1-acryloyl-2-cyanoindoles; [bis(difluoroacetoxy)iodo]benzene; catalyst-free